Improving phlebotomy handover of untaken blood tests to junior doctors. Issue 1 (27th August 2015) - Brown, Emily; Jarrett, Helen; Churchhouse, Gabrielle; Hartley, Matthew; Cohen, David; Kyprianou, Katerina; Murphy, Sarah; Walker, Brindley; Hill, Catherine
Abstract: A lack of communication between junior doctors and phlebotomists means untaken blood tests are often not recognised until late in a junior doctor's day, resulting in additional hours worked, delays in patient management, and potentially avoidable handover of additional work to on-call doctors. We set out to improve communication, with an aim that ward doctors should be made aware of patients who have not been successfully bled by phlebotomists by 1:00pm. By introducing a formal handover clipboard in a designated ward space, we facilitated communication between phlebotomists and doctors, and minimised the potential for unrecognised "missed" blood tests. Our intervention was met with approval; 88% of junior doctors surveyed stated they found the clipboards useful, and 74% have noticed an improvement in communication, working efficiency and better patient safety. Post-intervention, junior doctors knew about 70% of booked blood tests that had not been taken by 1:00pm, compared to 26% pre-intervention. By allowing the recognition of missed blood tests to be noted early enough in the day for repeat samples to be taken, and the results to be acted upon, we feel our intervention has been a success. As a group of new foundation doctors we have felt empowered that as a result of recognising a problem, implementing simple changes, and monitoring results we have made a genuine improvement to multi-disciplinary team working, workload of junior doctors, and patient safety.